PUISI TONTONAN LAN TUNTUNAN, ADEP KANAN LAN ADEP KIRI, DAN KALIYUGA LAN KILAYUGA KARYA I MADE SUARSA: ANALISIS STRUKTUR DAN SEMIOTIK - Ariadi, Ni Luh Alit (Humanis; Volume 6. No. 1. Januari 2014, 2014)
This study discusses the Poetry Tontonan lan Tuntunan, Adep Kanan lan Adep Kiri, and Kaliyuga lan Kilayuga works I Made Suarsa Structural Analysis and Semiotics, as for the purpose of this research is to investigate the structure and meaning of poetry symbolized Tontonan lan Tuntunan, Adep Kanan lan Adep Kiri, and Kaliyuga lan Kilayuga. The theory used in this study is the theory of the structure and semiotics. The method used in this study through three stages, namely the stage of data collection, the data analysis stage, stage presentation of data. Results obtained from the structure of the poem Tontonan lan Tuntunan, Adep Kanan lan Adep Kiri, and Kaliyuga lan Kilayuga works I Made Suarsa which includes: (1) typography, (2) a sound, (3) diction, (4) the language style include: a style of rhetoric and style of figurative language, (5) imagination, and (7) the thought contained in the poem include: theme and mandate. While the study revealed semiotics unfold the meaning of Existentialism in the poem Tontonan lan Tuntunan, the meaning of Pragmatism in the poem Adep Kanan lan Adep Kiri, the meaning of Induvidualisme in the poem Kaliyuga lan Kilayuga, and the meaning of Karma Phala in the third poem.
Keywords: Poetry, Structure, and Semiotics. (1)